ANALISIS ISLAMIC SERVICE QUALITY PADA KUALITAS PENDIDIKAN PONDOK PESANTREN AL ROSYID KABUPATEN BOJONEGORO DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS - Shoffan Maulana; Ilmiawan Auwalin (Universitas Airlangga, 2019)
Education is one aspect of development that is included in non-physical development. Therefore, it is important to assurance the quality of education in order to have an impact on sustainable development in various fields, especially human resources and the economy of a country. This study uses the Importance Performance Analysis method to measure how far the performance results are towards the expected level of importance of Al Rosyid Islamic Boarding School students in Bojonegoro. This research is focused on the quality of Islamic boarding school education, this is because Islamic boarding schools are Islamic education in Indonesia most of which are based in the regions. So this can be used as a reference for assessing the quality of education for Islamic boarding schools in regional areas to enhance human and economic development. The results of this study indicate that students there are satisfied with the results of the performance of Islamic boarding schools in managing education both academic, non-academic, and diniyah. Although said to be satisfied, the expectations of students and some boarding school dwellers still do not meet the values determined by them. Most still expect improvements. Therefore this study is very necessary for decision makers to be able to see new perspectives in non-physical based development, especially in the field of sustainable education.Keywords: economy, development, economic development, Islamic economic development, education, quality of education, Islamic boarding school